Red-NIR luminescence of Mo6 monolayered assembly directly anchored on Au(001). Issue 9 (1st July 2019) - Kepenekian, Mikaël; Molard, Yann; Costuas, Karine; Lemoine, Pierric; Gautier, Régis; Ababou Girard, Soraya; Fabre, Bruno; Turban, Pascal; Cordier, Stéphane
Abstract : The designed cluster [Mo6 Br i 8(NCS) a 6] 2− retains its multicomponent near infrared emission despite being in direct contact with a crystalline gold surface. Abstract : A tailored near infrared luminescent Mo6 octahedral cluster bearing thiocyanate (NCS) terminal ligands, [Mo6 Br i 8(NCS) a 6] 2−, has been synthesized to anchor onto a gold substrate. After immobilization, [Mo6 Br i 8(NCS) a 6] 2− building blocks form a self-assembled monolayer on the Au(001) surface as shown by scanning tunneling microscopy, atomic force microscopy and X-ray photoelectron spectroscopy. Strikingly, the photoluminescence of [Mo6 Br i 8(NCS) a 6] 2− observed in the powder precursor remains after grafting on Au(001). No quenching effect was observed despite the vicinity of the flat metal surface unlike most of the molecular luminophors. Periodic and molecular computational investigations based on density functional theory show that optical properties originate from the Mo6 Br i 8 core and are protected by the NCS outer sphere, despite the shortness of the anchors.